Diagnostic Value of 18F-NOTA-FAPI PET/CT in a Rat Model of Radiation-Induced Lung Damage - Qin, Xueting; Wang, Shijie; Liu, Xiaoli; Duan, Jinghao; Cheng, Kai; Mu, Zhengshuai; Jia, Jing; Wei, Yuchun; Yuan, Shuanghu (Frontiers in Oncology, 2022)
In this study, we explore the diagnostic value of a novel PET/CT imaging tracer that specifically targets fibroblast activation protein (FAP), 18F-NOTA-FAPI, in a radiation induced lung damage (RILD) rat model. High focal radiation (40, 60, or 90 Gy) was administered to a 5-mm diameter area of the right lung in Wistar rats for evaluation of RILD induction. Lung tissues exposed to 90 Gy radiation were scanned with 18F-NOTA-FAPI PET/CT and with 18F-FDG. Dynamic 18F-NOTA-FAPI PET/CT scanning was performed on day 42 post-irradiation. After in vivo scanning, lung cryosections were prepared for autoradiography, hematoxylin and eosin (HE) and immunohistochemical (IHC) staining. An animal model of RILD was established and validated by histopathological analysis. On 18F-NOTA-FAPI PET/CT, RILD was first observed on days 42, 35 and 7 in the 40, 60 and 90 Gy groups, respectively. After treatment with 90 Gy, 18F-NOTA-FAPI uptake in an area of RILD emerged on day 7 (0.65±0.05 %ID/ml) and reappeared on day 28 (0.81±0.09 %ID/ml), remaining stable for 4–6 weeks. Autoradiography and HE staining IHC staining revealed that 18F-NOTA-FAPI accumulated mainly in the center of the irradiated area. IHC staining confirmed the presence of FAP+ macrophages in the RILD area, while FAP+ fibroblasts were observed in the peripheral area of irradiated lung tissue. 18F-NOTA-FAPI represents a promising radiotracer for in vivo imaging of RILD in a dose- and time-dependent manner. Noninvasive imaging of FAP may potentially aiding in the clinical management of radiotherapy patients.